(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Green revolution in Punjab initiated the process of commercialization of agriculture leading to wide increase in agricultural productivity and profits to farmers.It resulted in enormous growth oppurtunities and rise in standard of living .It put Punjab on top indexes in terms of GDP in India. The mammoth size of growth concluded in some unwanted consequences in terms of unsustainable ecology. The present paper focuses on measuring the extent of commercialization of agriculture in different decades since 1971 and variations in different districts of Punjab with the help of percentages.